The black-litterman model in central bank practice: study for Turkish Central Bank - Ganikhodjaev, Nasir; Bayram, Kamola (Institute for Mathematical Research (INSPEM) Universiti Putra Malaysia, 2016)
The Modern Portfolio Theory is based on Markowitz Mean-Variance portfolio optimization. The Black-Litterman Model uses a Bayesian approach which combines expert’s views about assets involved in optimization with equilibrium returns implied by market capitalization weights, and as a result we get expected returns which can be put in MeanVariance optimization. After the global financial crisis 2007-2009 emerging countries’ central banks started to restructure their international reserves. During the crisis gold outperformed other assets by 42% and thus explicitly demonstrated its feature as safe haven asset. Therefore, including gold into the investment portfolio helps to survive economic turbulence with less harm. However, the question what percentage of portfolio should be allocated to gold to avoid the above mentioned problem remains unanswered. In this paper using the Black-Litterman model we consider this problem in case of the Central Bank of the Republic of Turkey